Spectral based damage identification technique on an earthen mock-up construction tested on a shaking table - Masciotta, M. G. (2014)
Conservation of ancient built heritage plays a leading role for modern societies. Knowledge about ancient building methods, essentially based on the use of natural materials such as earth, stone and wood, is fundamental to plan interventions aimed at preserving the architectural heritage. Due to the growing research on sustainable technologies, the interest in structural systems built using natural materials has been rising more and more. Taking an earthen mock-up construction as model, the paper focuses on the dynamic behaviour of such a system tested on a shaking table. Detailed descriptions of the model, its mechanical features, the seismic test performed and the damage pattern obtained are first presented. Then, the dynamic identification of the structure during damage occurrence is performed through the decomposition of the power spectral density matrix. Damage evolution and localization are also analyzed by an index based on the complex eigenvectors estimated from the matrix. Finally, comparisons between experimental and analytical results are addressed.